Formação e trabalho docente em tempos de meritocracia: reflexões sobre a política educacional nacional e sua convergência na formação continuada da rede municipal de Dois Vizinhos-PR - Mateus, Tatiane (2018)
This research shows how the ideology of meritocracy in liberal and neoliberal thinking is manifested in the conceptions and proposals for the teaching work in Brazilian education and, specifically, in the municipal network of Dois Vizinhos-PR in the period from 2013 to February 2018. The school, inserted in a capitalist society, by influence of this political and economic side, is now considered as a commodity. Thus, the nature of the problem of this research is part of this context, in order to analyze how the politics of meritocracy in the formation and in the teaching work is manifested. To this end, the "Partners of Education" Movement, which is designated as an entity of civil society, has been the subject of research and is the author of references for the elaboration of hegemonic educational policies. The purpose of this research is to understand the conception of meritocracy in training and teaching work in the "Education Partners", identifying the presence of this conception in the current National Education Plan as well as in teacher training, especially in the training proposal developed by Municipal Secretary of Education of Dois Vizinhos, State of Paraná. The methodology of the research was developed from the perspective of qualitative research, through the use of documental and bibliographic research. The following authors of the analyzes were used: Luiz Carlos de Freitas (2011, 2012), Gaudêncio Frigotto (2006, 2015), Dermeval Saviani (1987, 2001, 2005, 2007, 2010) Luiz Antônio Cunha (1980), Karel Kosik (1976). The principles of liberalism are briefly presented and how they justify meritocracy, which is at the origin of this doctrine. Through the ontological, epistemological and political foundations of this concept, meritocracy will be contextualized in times of neoliberal state and the establishment of new attributions to the teaching work. Subsequently, it analyzes the NGO (Non-Governmental Organization) "Partners in Education" and investigates the trend on the ideology of meritocracy in one of its documents: "The transformation of the quality of public basic education in Brazil", published in 2010, highlighting how the ideology of meritocracy and the proposals of the "Partners of Education" are materialized in the National Education Plan (2014-2024) with regard to the teaching work. Finally, an analysis of the continuing education of teachers in the municipal network of Dois Vizinhos-PR is carried out, revealing how the ideology of meritocracy is reproduced in this context. It is concluded that the ideology of meritocracy is a trend that has been consolidating in the continuous formation of teachers, from the educational policy of the Brazilian State to the specificity of the municipal network of Dois Vizinhos-PR. Its objective is to form the new human type suitable to neoliberalism and post-Fordism: the multipurpose subject, self-entrepreneur, individualist and competitive. To form this new human type in the public school, hegemonic educational policy requires the teacher training in the perspective of the pedagogy of skills - learning theory, while imposing the accountability to teachers for the results of education.